Bank Size, Financing Risk, And Efficiency Level On The Liquidity Of Islamic Banking In Indonesia - Febrina Dwi Cahyani (International Journal of Economics, Business and Innovation Research, 2024)
Liquidity problems must be anticipated by Islamic banks. To prevent bank runs (massive withdrawal of bank customer funds) that cause public distrust of Islamic banks as a whole, it needs to be handled immediately. This study aims to determine the effect of company size variables, financing risk and efficiency level (BOPO) on liquidity (FDR) of Islamic banks listed on the Indonesia Stock Exchange for the period 2018-2022. Research data obtained from annual reports of banking companies listed on the Indonesia Stock Exchange for the period 2018-2022. This study was analyzed by multiple linear regression analysis (multiple regression) using the E-Views 10 program. Partially, the company size variable has an effect on bank liquidity and the financing risk variable and the efficiency level do not have a significant effect on the liquidity of Islamic banks listed on the IDX. simultaneously the three variables affect the liquidity of Islamic banking. it is hoped that further research can increase the number of variables that have not been used and increase the number of samples not only Islamic banking listed on the IDX but can also use conventional banks and other sectors.